2021
DOI: 10.1111/bjh.17993
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3β/CCR6‐positive bone marrow cells correlate with disease activity in multicentric Castleman disease‐TAFRO

Abstract: Multicentric Castleman disease-thrombocytopenia, anasarca, reticulin fibrosis of bone marrow, renal dysfunction and organomegaly (MCD-TAFRO) -is an emergent phenotype characterized by lymphoproliferation, fluid collection, hemocytopenia and multiple organopathy. Although studies have demonstrated an aberrant blood cytokine/chemokine profile referred to as "chemokine storm", the pathogenesis remains unclear. We aimed to identify pathogenic key molecules, potential diagnostic targets and therapeutic markers in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Bacterial infection [29] Toxic epidermal necrolysis [33] Cyclosporine A Hepatotoxicity [20,30,[34][35][36] Renal toxicity [37] Thrombotic microangiopathy [38] Combination therapy with glucocorticoid Tocilizumab Bacterial infection [20,[39][40][41][42][43] CMV infection [37,[43][44][45][46] Fungal infection [40,42] Cyclosporine A…”
Section: Tocilizumabmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial infection [29] Toxic epidermal necrolysis [33] Cyclosporine A Hepatotoxicity [20,30,[34][35][36] Renal toxicity [37] Thrombotic microangiopathy [38] Combination therapy with glucocorticoid Tocilizumab Bacterial infection [20,[39][40][41][42][43] CMV infection [37,[43][44][45][46] Fungal infection [40,42] Cyclosporine A…”
Section: Tocilizumabmentioning
confidence: 99%
“…Although cyclosporine A has been widely used in the treatment of TAFRO syndrome [13], information regarding cases treated using tacrolimus remains limited. To the best of our knowledge, only four studies have reported the use of tacrolimus treatment for TAFRO syndrome [20,38,55,56] (Table 2), excluding one in which the duration of tacrolimus use was markedly short to evaluate its efficacy [33]. Among these studies, we first described two cases of TAFRO syndrome that were successfully treated using tacrolimus [20].…”
Section: Rituximabmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some researchers have demonstrated that TAFRO syndrome and iMCD-TAFRO are different disease entities, they share similar pathophysiologies involving cytokine storms [ 2 , 4 , 7 ]. For instance, elevated levels of interferon (IFN) γ-inducible protein 10 kDa, IL-10, IL-23, chemokine C-X-C motif chemokine ligand (CXCL) 13, IL-6, and VEGF are reported in iMCD-TAFRO, whereas elevated levels of IL-6 and VEGF are seen in TAFRO syndrome [ 24 , 25 , 26 , 27 , 28 ]. The Janus kinase/signal transducers and activators of transcription (JAK/STAT) and phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathways have been suggested to be involved in the cytokine storms seen in iMCD-TAFRO and TAFRO syndrome [ 4 , 28 ].…”
Section: Tafro Syndrome and Cytokine Stormsmentioning
confidence: 99%
“…Abe et al. also performed proteomic analysis of multiple serum cytokines/chemokines in six patients with MCD‐TAFRO in remission versus nonremission 34 . Significant changes in chemokine and growth factor levels (e.g., CCL2/MCP1, CCL5/RANTES, and CHI3L1) were found after successful treatment of TAFRO syndrome with cyclosporine or tocilizumab.…”
Section: Pathogenesismentioning
confidence: 99%